Blood Lead Levels of Children Using Traditional Indian Medicine and Cosmetics: A Feasibility Study - Julia Keosaian MPH; Thuppil Venkatesh PhD; Salvatore D’Amico BS; Paula Gardiner MD, MPH; Robert Saper MD, MPH (Global Advances in Health and Medicine, 2019)
Background Traditional Indian cosmetics and Ayurvedic medicines may contain lead. Previous studies have shown a relationship between eye cosmetic use (kohl) in children and elevated blood lead levels (BLLs) > 10 µg/dL. However, an association between Ayurvedic use and elevated BLLs in children is unknown and understudied. Methods We assessed the feasibility of collecting BLLs in children attending Ayurvedic outpatient settings in India. Our pilot study took place over 3 days in the summer of 2010 at a large public Ayurveda hospital and a small pediatric clinic in southern India. Using a trained interpreter, we administered a standardized questionnaire in Malayalam, assessing sociodemographics, Ayurvedic medicine use, kohl use, and other potential risk factors for lead exposure, to parents of pediatric outpatients. We also analyzed BLLs using a portable lead analyzer. Results The study enrolled 29 children (mean age, 3.8 years). The mean BLL was 6.7 µg/dL (SD = 3.5; range, 3.5–20.2). Seventy-two percent of the children used Ayurvedic medicine in the past 2 years and 55% reported kohl use. Mean BLL of Ayurvedic users and nonusers was 6.2 µg/dL and 8.5 µg/dL, respectively ( P  = .08). Kohl users had a statistically significant higher BLL than nonusers (8.0 µg/dL vs 5.3 µg/dL, P  = .03). Conclusions It is feasible to collect BLLs in pediatric Ayurvedic outpatient clinics in southern India. Collaborative relationships with community members and hospital staff were essential. Further research is needed to investigate Ayurveda and kohl use as risk factors for elevated lead burden among Indian children.